Pengaruh Struktur Modal Dan Profitabilitas Terhadap Nilai Perusahaan - D. Muhammad Yamin (E-Journal Studia Manajemen, 2023)
Company value is a value used by investors to assess the success rate of the company, the higher the company value reflected in the stock price, the higher the level of investor confidence in the company. This study aims to examine the effect of Capital Structure and Profitability on Firm Value in Food and Beverage Companies listed on the Indonesia Stock Exchange (IDX). The data used is secondary data with the documentation method in the form of annual financial reports of Food and Beverage Companies listed on the Indonesia Stock Exchange (IDX) for the 2020-2022 period taken from the official website of the Indonesia Stock Exchange (IDX) www.idx.co.id. The population in this study amounted to 84 food and beverage companies, the sample was taken using purposive sampling method, namely based on certain criteria as many as 20 companies. The analysis technique used is the classical assumption test, multiple linear regression determination coefficient test and hypothesis testing using SPSS version 25. The results of the study are Capital Structure partially has no influence on Firm Value. Profitability partially has an influence on Firm Value. Capital Structure and Profitability simultaneously have an influence on Firm Value